1994ネン ショシュン オヨビ ショカ ノ ナンキョク ショウワキチ シュウヘン ノ テイチャク ヒョウカ デ サイシュウ サレタ チンコウ リュウシ ノ ソセイ - 齋藤, 良子; サイトウ, リョウコ; 工藤, 栄; クドウ, サカエ; 佐藤, 壽彦; サトウ, トシヒコ; 渡辺, 研太郎; ワタナベ, ケンタロウ; 福地, 光男; フクチ, ミツオ; Saito, Ryoko; Kudoh, Sakae; et al. (1998)
P(論文) 1994年の初春(8月12日～9月2日)及び初夏(11月27日～12月17日)の期間に, 昭和基地近くに係留したセディメントトラップに捕集された沈降粒子の顕微鏡観察を行った。形状や形態の特徴から識別された沈降粒子ごとの計数及び計測を行い, それぞれの沈降粒子束(フラックス)を見積もった。識別できた沈降粒子は, 珪藻類と動物プランクトンの糞と思われる粒子であり, 珪藻類として中心目が11属, 羽状目が9属, 糞粒として4タイプが識別できた。初春の珪藻類及び糞粒のフラックスは低い値を示したが, 初夏になると増加した。特に珪藻細胞数は2桁の増加がみられた。また, 珪藻類の優占種及び, 糞粒の優占型には, 季節遷移が認められた。容積フラックスにおいて, 初春には, 珪藻類では中心目のCorethron criophilum, 糞粒では丸型が多かったが, 初夏になると珪藻類では羽状目が, 糞粒では円筒型が組成は高い割合を示し, 水柱平均では30倍以上の増加が認められた。この初春と初夏で容積フラックスの季節的変化を示したが, 珪藻粒子と糞粒との容積比を水柱平均にすると, 大きな変化が認められなかった。 Sinking particles collected in several sediment trap experiments near Syowa Station in austral spring-summer in 1994 have been microscopically analyzed. From the features of the shape and morphology, collected particles were identified, enumerated and measured, and the flux of each identified species was estimated. The majority of the particles were composed of diatom cells and "fecal pellet"-like aggregates were recognized in the samples. In spring, the particle fluxes were rather low and higher fluxes were detected in summer. In particular, diatom cell flux increased by two order of magnitude. The composition of the sinking particles varied seasonally; a centric diatom, Corethron criophilum, and round-shape fecal pellets accounted for dominant diatom cell and fecal pellet fluxes in the spring. But pennate diatoms and collumn-shape pellets dominated in summer. The vertical flux varied, too. In spite of the significant difference of total bio-volume flux between spring and summer (>30 times higher in summer), the bio-volume ratio, such as total identified diatoms and fecal pellets, stayed rather constant. departmental bulletin paper